Role of Libraries in Preservation of Traditional Knowledge: - Dangi, Ram Kumar; Saraf, Sanjiv (Qualitative and Quantitative Methods in Libraries, 2019)
The article discusses the concept of traditional knowledge, its importance, role of libraries and information centers in preservation of traditional knowledge in India. Libraries and Information centers are performing various activities to preserve traditional knowledge e.g. documentation of traditional knowledge, capturing/recording of traditional knowledge, microfilming of traditional knowledge, digitization of traditional knowledge and creating digital repositories to enhance the accessibility of traditional knowledge. In India, various libraries and information centers are engaged in preservation of traditional knowledge e.g. National Manuscript Mission (NMM), Traditional Knowledge Digital Library (TKDL), and National Digital Library of India (NDLI) etc. Some challenges are also being faced by above organizations e.g. lack of recording of traditional knowledge, copyright issues, cost of digitization and lack of trained manpower.